The relationship between serum bilirubin concentration and coronary artery ectasia - Demir, Mehmet; Demir, Canan; Keçeoğlu, Serdar (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : The pathophysiology of coronary artery ectasia (CAE) has not been clearly identified, although multiple abnormalities including arteritis, endothelial dysfunction, and atherothrombosis have been reported. Several studies have demonstrated that higher serum bilirubin inhibits the inflammation and proliferation of vascular smooth muscle cells; also there is a relationship between serum bilirubin and cardiovascular disease. However, the relationship between bilirubin and CAE is still unknown. Aim : We compared serum bilirubin concentration between CAE patients and controls. Material and methods : This study included 50 CAE patients (20 male, mean age: 60.26 ±10.6 years) and 30 control persons (10 male, mean age: 57.86 ±11.6 years). These participants underwent concurrent routine biochemical tests and leukocyte count, hemoglobin, hematocrit and platelet count in whole blood. These parameters were compared between groups. Results : No statistically significant difference was found between the two groups in terms of basic characteristics. Total, direct and indirect serum bilirubin levels were significantly lower among persons with CAE patients than controls (0.37 ±0.4 vs. 0.71 ±0.6 and 0.13 ±0.1 vs. 0.27 ±0.2 and 0.24 ±0.2 vs. 0.43 ±0.4 mg/dl; all p < 0.001, respectively). Conclusions : Our study revealed a relationship between serum bilirubin and CAE.